Quality of Motor Vehicle Tax Payment Services at The Joint Samsat Office in Bangkalan Regency - Adelia Putri Utami; Tukiman Tukiman (Jurnal Kebijakan Publik, 2025)
SAMSAT (One Roof Integrated Administration System) is a government institution in Indonesia that is tasked with managing motor vehicle administration. Samsat also functions to facilitate the administration of motor vehicles, especially in the issuance of STNK, TNKB (vehicle registration plate), Motor Vehicle Tax Payment (PKB), Motor Vehicle Transfer Fee (BBNKB), and Mandatory Contributions to Road Traffic Accident Funds. The Samsat Office operates with the aim of providing fast, efficient, and transparent services to the public. The purpose of this study is to describe and analyze the Quality of Payment Services. The method used is descriptive qualitative, using observation and interview techniques. The results of the study The Joint Samsat Office of Bangkalan Regency is obliged to satisfy its customers as a public service organization. This is one effort to increase public satisfaction in terms of service quality. The author will describe the data analysis in accordance with the research plan that has been in the research proposal on the Quality of Motor Vehicle Tax Payment Services at the Joint Samsat Office of Bangkalan Regency after summarizing the results of the study in the form of interviews and other supporting data related to the Bangkalan Samsat Office. There are several dimensions of service quality at the Samsat Office that are still lacking, so it requires improvement in the performance of employees/apparatus at the Samsat office in Bangkalan Regency.